Charmonium properties in the quark-gluon plasma - Gert Aarts (The XXV International Symposium on Lattice Field Theory (LATTICE 2007) - Nonzero temperature and density, 2008)
We present results for charmonium correlators and spectral functions in 2-flavour CD on anisotropic lattices. Our results indicate that the S-waves (J/psi and eta_c) survive up to temperatures close to 2T_c, while the P-waves (chi_c0 and chi_c1) melt away below 1.2T_c.